Prognosis of patients with and without septal substrate after VT ablation due to electrical storm. (19th May 2022) - Mueller, J; Nentwich, K; Berkovitz, A; Halbfass, P; Ene, E; Sonne, K; Simu, GR; Chakarov, I; Deneke, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Data about VT ablation in patients with electrical storm (ES) is limited. This study sought to compare the prognostic outcome of patients undergoing VT ablation after electrical storm with and without a septal substrate on mortality, VT recurrence rates, rehospitalization rates and major adverse cardiac events (MACE). Methods: In this large single-centre study patients presenting with ES and undergoing VT ablation were included from June 2018 to April 2021. Patients with septal substrate were compared to patients without septal substrate. The primary prognostic outcome was cardiovascular mortality, secondary endpoints were VT recurrence rates, rehospitalization rates and MACE all after a median follow-up of 22 months. Results: A total of 108 patients underwent a first VT ablation due to electrical storm and were included (65 ± 13 years; 86% male; 45% ischemic cardiomyopathy). Cardiovascular risk factors were equally distributed among both groups (all p>0.05). Major complications occurred in 11% of all patients with increased postinterventional third degree AV blocks among patients with septal substrate (9% vs 0%; p=0.062). Noninducibility of the clinical VT was achieved in 98% of all patients without a septal substrate and in 91% of all patients with a septal substrate (p=0.136). Noninducibility of any VT was achieved in 88% without a septal substrate and in 66% with a septal substrate (p=0.011). However, in non-invasive programmed stimulation before hospital discharge VT inducibility did not differ among both groups (p>0.05). After 1 year and a median of 22 months follow-up, patients with septal substrate died significantly more often due to cardiovascular causes (25% vs. 7%; log-rank p=0.021). In univariate analysis cardiovascular mortality for ES patients with septal substrate was 3.9 fold higher (HR 3.979; CI 95% 1.124 – 14.092; p=0.032). Independent predictors of adverse outcome in multivariable regression analysis were presence of septal substrate (HR 4.836; p=0.026) and increased numbers of VTs inducible during VT ablation (HR 1.635; p=0.007). VT recurrence during follow-up was 59% and equally distributed among both groups (log rank p=0.911). Rehospitalization rates (log rank p=0.532) and rates of MACE (log rank p=0.463) were equal. Conclusions: Presence of a septal substrate is associated with adverse long-term cardiovascular mortality in patients admitted for VT ablation after electrical storm. Despite decreased ablation success in these patients VT recurrence rates were not increased during follow-up.